From problem solving to modeling – the emergence of models and modeling perspectives - Mousoulides, Nicholas; Sriraman, Bharath; Christou, Constantinos (NOMAD Nordic Studies in Mathematics Education, 2007)
More than 25 years ago, a research project in the U.S investigated the question: ”What is needed by students, beyond having a mathematical idea, that enables students to use the mathematical idea in everyday problem solving situations? (Lesh, Landau & Hamilton, 1983). The answer to this question has begun to emerge after 25 years of systemic work in the domain of modeling. In this paper, we chronicle the emergence of models and modeling perspectives (MMP) from the genre of problem solving research via a synthesis of the major strands in the extant literature.